Antifungal effect of phenolic extract of fermented rice bran with Rhizopus oryzae and its potential use in loaf bread shelf life extension. (5th June 2018) - Denardi‐Souza, Taiana; Luz, Carlos; Mañes, Jordi; Badiale‐Furlong, Eliana; Meca, Giuseppe
Abstract: BACKGROUND: In this study the antifungal potential of a phenolic extract obtained from rice bran fermented with Rhizopus oryzae CECT 7560 and its application in the elaboration of bread was assessed. RESULTS: Eighteen compounds with antifungal potential were identified by LC‐ESI‐qTOF‐MS in the extract: organic acids, gallates and gallotannins, flavonoids, ellagic acid and benzophenone derivatives. The extract was active against strains of Fusarium, Aspergillus and Penicillium, with minimum inhibitory concentration ranging from 390 to 3100 µg mL −1 and minimum fungicidal concentration variable from 780 to 6300 µg mL −1 . The strains that were most sensitive to the phenolic extract were F. graminearum, F. culmorum, F. poae, P. roqueforti, P. expansum and A. niger . The phenolic extract added at 5 and 1 g kg −1 concentrations in the preparation of bread loaves contaminated with P. expansum produced a reduction of 0.6 and 0.7 log CFU g −1 . The bread loaves treated with calcium propionate and 10 g kg −1 of the phenolic extract evidenced an improvement in their shelf lives of 3 days. CONCLUSION: The phenolic extract assessed in this study could be considered as an alternative for inhibiting toxigenic fungi and as a substitute for synthetic compounds in food preservation. © 2018 Society of Chemical Industry